Sympagic Fauna in and Under Arctic Pack Ice in the Annual Sea-Ice System of the New Arctic - Ehrlich, Julia; Schaafsma, Fokje L.; Bluhm, Bodil A.; Peeken, Ilka; Castellani, Giulia; Brandt, Angelika; Flores, Hauke (Frontiers in Marine Science, 2020)
A strong decline and thinning of the Arctic sea-ice cover over the past five decades has been documented. The former multiyear sea-ice system has largely changed to an annual system and with it the dynamics of sea-ice transport across the Arctic Ocean. Less sea ice is reaching the Fram Strait and more ice and ice-transported material is released in the northern Laptev Sea and the central Arctic Ocean. This trend is expected to have a decisive impact on ice associated (“sympagic”) communities. As sympagic fauna plays an important role in transmitting carbon from the ice-water interface to the pelagic and benthic food webs, it is important to monitor its community composition under the changing environmental conditions. We investigated the taxonomic composition, abundance and distribution of sea-ice meiofauna (here heterotrophs >10 μm; eight stations) and under-ice fauna (here metazoans >300 μm; fourteen stations) in Arctic 1.5 year-old pack ice north of Svalbard. Sampling was conducted during spring 2015 by sea-ice coring and trawling with a Surface and Under-Ice Trawl. We identified 42 taxa associated with the sea ice. The total abundance of sea-ice meiofauna ranged between 580 and 17,156 ind.m–2 and was dominated by Ciliophora (46%), Copepoda nauplii (29%), and Harpacticoida (20%). In contrast to earlier studies in this region, we found no Nematoda and few flatworms in our sea-ice samples. Under-ice fauna abundance ranged between 15 and 6,785 ind.m–2 and was dominated by Appendicularia (58%), caused by exceptionally high abundance at one station. Copepoda nauplii (23%), Calanus finmarchicus (9%), and Calanus glacialis (6%) were also very abundant while sympagic Amphipoda were comparatively rare (0.35%). Both sympagic communities showed regional differences in community composition and abundance between shelf and offshore stations, but only for the under-ice fauna those differences were statistically significant. Selected environmental variables moderately explained variations in abundances of both faunas. The results of this study are consistent with predictions of diversity shifts in the new Arctic.